2010
DOI: 10.1080/02626660903546167
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear analysis of seasonality and stochasticity of the Indus River

Abstract: One of the world's largest irrigation networks, based on the Indus River system in Pakistan, faces serious scarcity of water in one season and disastrous floods in another. The system is dominated both by monsoon and by snow and glacier dynamics, which confer strong seasonal and inter-annual variability. In this paper two different forecasting methods are utilized to analyse the long-term seasonal behaviour of the Indus River. The study also assesses whether the strong seasonal behaviour is dominated by the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 66 publications
(93 reference statements)
2
26
0
Order By: Relevance
“…For instance, Kędra (2014) investigated discharge dynamics of the Raba River in southern Poland using several independent methods and concluded that underlying dynamics are not random but deterministic. Similar results were recently obtained by Hassan and Ansari (2010), Xu et al (2010), Sivakumar and Singh (2012), Khatibi et al (2012), and Kalteh and Berndtsson (2007). These studies suggested that streamflow dynamics are nonlinear and persistent complexity can be analyzed by a nonlinear chaotic approach to gain new insights.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…For instance, Kędra (2014) investigated discharge dynamics of the Raba River in southern Poland using several independent methods and concluded that underlying dynamics are not random but deterministic. Similar results were recently obtained by Hassan and Ansari (2010), Xu et al (2010), Sivakumar and Singh (2012), Khatibi et al (2012), and Kalteh and Berndtsson (2007). These studies suggested that streamflow dynamics are nonlinear and persistent complexity can be analyzed by a nonlinear chaotic approach to gain new insights.…”
Section: Introductionsupporting
confidence: 84%
“…In this study, we employed a zeroorder local forecasting model (Farmer and Sidorowich 1987) since it has fewer parameters to estimate in comparison to nth-order polynomial or local differential equations to avoid exponentially growing estimation errors (Hassan and Ansari 2010). This model approximates the local system dynamics by considering all k-neighbors of Y t as:…”
Section: Nonlinear Chaotic Modelmentioning
confidence: 99%
“…6b) helps to identify the order of autoregressive and existence of moving average components. It is very supportive in finding the seasonal autoregressive integrated moving average SARIMA models [1]. The crosscorrelation analyses shows that the local temperature (Chitral, Gilgit, Skardu) has significant influence on the river flow (Table 2, Fig.…”
Section: Methodssupporting
confidence: 60%
“…2). So, the time series methodology does not completely describe the hydrological variation of the Jhelum River like the Indus river flow at the Tarbela station result presented in Hassan & Ansari [1]. This may also observed from Jhelum river flow ACF plot has sharp roll off (in early lag values Fig.…”
Section: Proficiency Of the Modelmentioning
confidence: 91%
See 1 more Smart Citation